Expression of Endothelial Nitric Oxide Synthase in Testicular Cells of Men with Obstructive Azoospermia; a Case-Control Study - Novin, Marefat Ghaffari; Abed, Farhang; Hosseini, Mohammad Ali; Kiani, Fatemeh; Foghi, Khadijeh; Aliakbari, Fereshte (Archives of Men's Health, 2018)
Introduction: Obstructive azoospermia is one of the causes of post-testicular infertility in men and previous studies have reported inconsistent levels of endothelial nitric oxide synthase (eNOS) enzyme in these patients. Accordingly, the present study aimed to provide further evidence on the expression of eNOS enzyme in patients with azoospermia. Materials and Methods: In this case-control study, 10 patients, who were diagnosed with azoospermia and were referred to the infertility center for treatment or diagnosis, and 7 healthy fertile men were recruited. An informed written consent was obtained from included subjects and they underwent testicular biopsies. Samples were assessed via immunohistochemical methods to determine their levels of eNOS expression. Results: Both leydig and sertoli cells were found to express eNOS, while this enzyme was not expressed in normal germinal cells. The only significant difference between the two groups was the level of eNOS expression in sertoli cells which was found to be higher in patients with obstructive azoospermia compared to the control group (P<0.001). Conclusion: According to the results of this study, sertoli cells and their interactions with germinal cells of seminiferous tubule might play an important role in sperm quality and a subsequent successful fertilization.